Efektifitas Aplikasi Arabic Listening Speaking dalam Meningkatkan Kemahiran Berbicara Bahasa Arab Siswa: Studi Kasus di MA Al- Hidayah Pasuruan / The Effectiveness of Arabic Listening Speaking Application in Improving Students' Arabic Speaking Skills: A Case Study at MA Al-Hidayah Pasuruan - Muhamad Hujatul Islam; Mochamad Hasyim; Miftachul Taubah (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2025)
This study aims to test the effectiveness of the Arabic Listening Speaking application in improving students' maharah kalam at MA Al-Hidayah Pasuruan. The research method used is quantitative with a one group pretest and posttest experimental design, involving all students as research subjects. Data collection was carried out through pretest and posttest as well as classroom observation. The results of data analysis showed that there was a significant increase in maharah kalam ability, as indicated by the paired sample t-test significance value of 0.001. In addition, the N-Gain value of 60.98% showed an increase in the moderate category. The findings from the observation also strengthen that the use of the Arabic Listening Speaking application is able to create an interactive, innovative, and enjoyable learning atmosphere. Overall, this study makes a significant contribution to the development of Arabic language learning in Indonesia and confirms the positive potential of using technology to support the learning process.Abstrak: Penelitian ini bertujuan untuk menguji keefektifan aplikasi Arabic Listening Speaking dalam meningkatkan maharah kalam siswa di MA Al-Hidayah Pasuruan. Metode penelitian yang digunakan adalah kuantitatif dengan rancangan eksperimen one group pretest and posttest, dengan melibatkan seluruh siswa sebagai subjek penelitian. Pengumpulan data dilakukan melalui pretest dan posttest serta observasi kelas. Hasil analisis data menunjukkan bahwa terdapat peningkatan kemampuan maharah kalam yang signifikan, yang ditunjukkan dengan nilai signifikansi paired sample t-test sebesar 0,001. Selain itu, nilai N-Gain sebesar 60,98% menunjukkan peningkatan dalam kategori sedang. Temuan hasil observasi juga memperkuat bahwa penggunaan aplikasi Arabic Listening Speaking mampu menciptakan suasana belajar yang interaktif, inovatif, dan menyenangkan. Secara keseluruhan, penelitian ini memberikan kontribusi yang signifikan bagi pengembangan pembelajaran bahasa Arab di Indonesia dan menegaskan potensi positif penggunaan teknologi untuk mendukung proses pembelajaran.